Proposal “Deal of the Century” dan Dampaknya bagi Proses Perdamaian Palestina-Israel - Broto Wardoyo (Andalas Journal of International Studies (AJIS), 2021)
In January 2020, President Donald Trump put forward a peaceproposal which he claimed to be the “deal of the century”. It is apeace proposal that offers general framework on settlement ofborders, sovereignty of the Palestinian state, the status ofJerusalem, and refugees’ issue as well as a framework oneconomic cooperation between Palestine and Israel which Trumpinsisted as a fair final solution for the Palestinian-Israeli conflict.This article seeks to assess the impact of this proposal to thePalestinian-Israeli peace process. In doing so, this article comparesthis proposal with previous agreements and concludes that thisproposal brings negative, rather than positive, impacts to the peaceprocess since it is not based on a balance positioning between thetwo conflicting parties. This proposal strengthens Israeli’s claimand hence enhances their position in the negotiation whichindicating the inability of the United States to serve as an honestbroker to the peace process. In addition, this proposal was putforward by President Trump during an unfavorable condition inboth Palestinian and Israeli domestic politics. The only positiveaspect of this proposal is that it can serve as a reason to restartnegotiation process. Therefore, this proposal should be consideredonly as a steppingstone to open another round of peace negotiationbetween Palestine and Israel and should not be implemented as it is.